Relationship between stress and bruxism among university students: a cross-sectional study - de Oliveira, Dhelfeson Douglas; Brum-Júnior, Jadimar; Soares, Luana; Cerqueira, Wyllerson; Costa, Igor; Oliveira, Evandro; Gomes, Gabriela; Murta, Agnes; Tavano, Karine Taís; Galvão, Endi; Gonçalves, Patricia; Dumont Flecha , Olga (Revista Estomatología, 2021)
Background: Bruxism is defined as repetitive masticatory muscle activity characterized by clenching or grinding of the teeth and it has been related to psychological factors, such as personality traits, anxiety and stress. Objective: To investigate association between stress and bruxism among university students. Materials and methods: Lipp’s Stress Symptoms Inventory for Adults (LSSI) was applied to 253 university students in Diamantina, Brazil. They were clinically evaluated to verify dental wear. The non-instrumental evaluation of probable bruxism was determined by the patients’ reports. Sociodemographic variables and self-reported stress data were collected by using the questionnaire. The chi-square test was used, and significance level of 5% (p<0.05) was adopted. Results: The prevalence of bruxism was 45.8% and stress, 37.9%. There was no significant association between the presence of stress diagnosed by ISSL and bruxism (p = 0.815). Among the students diagnosed as stressed, 31.6% were in the resistance phase. Self-reported stress was associated with the habit of tooth grinding (p < 0.001). Conclusions: No association was found between stress and bruxism. Nevertheless, the prevalence of bruxism among these students was considered high.